2014
DOI: 10.1016/j.neulet.2014.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sleep restriction elevates brain interleukin-1 beta and tumor necrosis factor-alpha and attenuates brain-derived neurotrophic factor expression

Abstract: Acute sleep loss increases pro-inflammatory and synaptic plasticity-related molecules in the brain, including interleukin-1beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and brain-derived neurotrophic factor (BDNF). These molecules enhance non-rapid eye movement sleep slow wave activity (SWA), also known as electroencephalogram delta power, and modulate neurocognitive performance. Evidence suggests that chronic sleep restriction (CSR), a condition prevalent in today's society, does not elicit the enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 32 publications
(61 reference statements)
6
72
0
1
Order By: Relevance
“…This pattern was previously revealed for TNF brain levels in animals, which substantiated the view of TNF being a sleep regulatory substance Zielinski et al, 2014). The difference in serum TNF levels between early sleep and nocturnal wakefulness was $0.2 pg/ml, which appears to be of considerable magnitude for an acute sleep manipulation of only few hours in healthy subjects, when compared to chronic clinical conditions like in obese subjects and sleep apnea patients with increments in circulating TNF of $0.5 and $1.0 pg/ml, respectively, with reference to healthy controls (Minoguchi et al, 2004).…”
Section: Tnf Levels In Blood and Unstimulated Tnf Production By Monocsupporting
confidence: 81%
See 1 more Smart Citation
“…This pattern was previously revealed for TNF brain levels in animals, which substantiated the view of TNF being a sleep regulatory substance Zielinski et al, 2014). The difference in serum TNF levels between early sleep and nocturnal wakefulness was $0.2 pg/ml, which appears to be of considerable magnitude for an acute sleep manipulation of only few hours in healthy subjects, when compared to chronic clinical conditions like in obese subjects and sleep apnea patients with increments in circulating TNF of $0.5 and $1.0 pg/ml, respectively, with reference to healthy controls (Minoguchi et al, 2004).…”
Section: Tnf Levels In Blood and Unstimulated Tnf Production By Monocsupporting
confidence: 81%
“…In accordance with its sleep regulating function, brain levels of endogenous TNF fluctuate with the sleep-wake cycle with a peak during the early resting time and a trough after elapsed sleep (Bredow et al, 1997;Cearley et al, 2003;Floyd and Krueger, 1997;Krueger et al, 1999). Moreover, during experimental sleep deprivation, spontaneous TNF production in the brain is increased (Taishi et al, 1999;Zielinski et al, 2014). However, this pattern characteristic for a sleep regulatory substance has not been obtained in human studies measuring circulating TNF levels in blood: 24 h observations revealed either no overt rhythm (Gudewill et al, 1992;Togo et al, 2009;Vgontzas et al, 2004) or a morning peak in levels of TNF (Vgontzas et al, 2002(Vgontzas et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Selective REM sleep deprivation up-regulated the levels of Zif268, Arc and BDNF during REM sleep rebound (66). In CSR, BDNF also increased in the cortex and hippocampus on SR1, immediately after 18 h sleep deprivation, but then decreased below baseline values on the following days (67). Interestingly, mRNA level of adenosine 2A receptor, critically involved in enhancing the effect of BDNF on hippocampal LTP (3,68), progressively increased in the hippocampus after CSR reaching significance on SR5 (69).…”
Section: The Pattern Of Rem Sleep Rebound Is Mirrored In Eeg Slowmentioning
confidence: 93%
“…The gene expression and protein levels of neurotrophic factors involved with cell growth and function (Boyd and Gordon 2003a, b) have also been shown to be affected by sleep deprivation (Cirelli and Tononi 2000a;Sei et al 2000;Fujihara et al 2003;Hamatake et al 2011;Ventskovska et al 2014;Wallingford et al 2014;Zielinski et al 2014). Most studies were concerned with BDNF, a neurotrophin of great importance for neuronal plasticity and survival (Ghosh et al 1994;Ventimiglia et al 1995;Lipsky and Marini 2007;Sossin and Barker 2007).…”
Section: Sleep Deprivation and Neurotrophic Factorsmentioning
confidence: 99%